PENCEGAHAN STUNTING MELALUI KEGIATAN TEMATIK “ISI PIRINGKU DENGAN MAKANAN BERGIZI” DI DESA SITIREJO BLORA - Siti Amaroh; Naila Uswatun Hasanah; Masturin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Stunting is a pressing public health issue in developing countries. This community service activity was conducted in Sitirejo Village, Blora Regency, Central Java Province. The program was carried out as part of the Integrated Community Service for Religious Moderation Competency (KKN-IKMB) with the theme